ASYMPTOTICS OF SOLUTIONS OF DIFFUSION STOCHASTIC DIFFERENTIAL-FUNCTIONAL SYSTEMS WITH A SMALL PARAMETER UNDER THE ACTION OF EXTERNAL RANDOM VARIABLES - Doroshenko, Iryna; Yasynskyy, Volodymyr (SWorldJournal, 2022)
The paper considers averaging in stochastic differential equations without aftereffects under the action of external fixed random variables. Then this technique of proofs is transferred to averaging for stochastic differential-functional equations under the action of external perturbations of the type of random variables (SDFRRV).
АСИМПТОТИКА РОЗВ’ЯЗКІВ ДИФУЗІЙНИХ СТОХАСТИЧНИХ ДИФЕРЕНЦІАЛЬНО-ФУНКЦІОНАЛЬНИХ СИСТЕМ З МАЛИМ ПАРАМЕТРОМ ПІД ДІЄЮ ЗОВНІШНІХ ВИПАДКОВИХ ВЕЛИЧИН
Keywords: stochastic differential equation; external perturbations; quasilinear stochastic systems with small parameter